Marc-Antoine Muret commentant les obscénités de Catulle - Siirak, Ülo (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
The French humanist Marc-Antoine Muret published his commentary on Catullus in the mid-16th century in Italy, where he had fled after teaching courses on the same poet in Bordeaux and Paris, and after associating with members of the Pléiade. Although his commentary follows the existing tradition, it also introduces several innovations, namely the treatment of Catullus' poetic and aesthetic aspects, even including his personal appreciation of the poet. Since almost half of Catullus' work contains passages which could be considered as obscene, Muret must address them in his commentary. In the following, we shall discuss, what to understand under obscenities in Catullus and the tactics of Muret in dealing with them. For exemple, at times, he avoids commenting on these passages - we cannot always establish the true cause of it - while at other times he adopts a strategy to create distance between himself and the text being commented upon, or he even comments with interpretations which increase the level of obscenity. In such case, his commentary is accompanied by a rather severe moral judgment.